Post-conversion sialylation of prions in lymphoid tissues - Srivastava, Saurabh; Makarava, Natallia; Katorcha, Elizaveta; Savtchenko, Regina; Brossmer, Reinhard; Baskakov, Ilia V. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Sialylated glycans on the surface of mammalian cells act as part of a “self-associated molecular pattern,” helping the immune system to recognize “self” from “altered self” or “nonself.” To escape the host immune system, some bacterial pathogens have evolved biosynthetic pathways for host-like sialic acids, whereas others recruited host sialic acids for decorating their surfaces. Prions lack nucleic acids and are not conventional pathogens. Nevertheless, prions might use a similar strategy for invading and colonizing the lymphoreticular system. Here we show that the sialylation status of the infectious, disease-associated state of the prion protein (PrPSc) changes with colonization of secondary lymphoid organs (SLOs). As a result, spleen-derived PrPSc is more sialylated than brain-derived PrPSc. Enhanced sialylation of PrPSc is recapitulated in vitro by incubating brain-derived PrPSc with primary splenocytes or cultured macrophage RAW 264.7 cells. General inhibitors of sialyltranserases (STs), the enzymes that transfer sialic acid residues onto terminal positions of glycans, suppressed extrasialylation of PrPSc. A fluorescently labeled precursor of sialic acid revealed ST activity associated with RAW macrophages. This study illustrates that, upon colonization of SLOs, the sialylation status of prions changes by host STs. We propose that this mechanism is responsible for camouflaging prions in SLOs and has broad implications.
Gesehen am 22.06.2020